Jual Beli Dalam Islam - Zailani Zailani (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
Buying and selling is one part of mualamalah. It is often found in society that the buying and selling process is not in accordance with Islamic principles. There are several trading conditions that are not implemented or do not follow the instructions of the Koran. This study aims to find out how the concept of buying and selling in Islam. The method used in this research is qualitative research, library research. By using the primary data source is from books, documents or other material, which is directly related to the research material. From this research, it was found that buying and selling must have several rules that can be used as guidelines, one of which is the honesty of both parties conducting transactions. Goods that are traded are substances that do not contain elements of impurity. There is no fraud in buying and selling. Between the seller and the buyer are both happy, ie there is no coercion from anywhere in the sale and purchase. Based on the attitude of mutual care and trust between one another.